Advocacy in English language teaching and learning - Linville, Heather A. (New York, NY : Routledge, 2019)
"This holistic text explores the nexus of advocacy and English language teaching and learning, beginning with theoretical examinations of advocacy, covering constraints and challenges, and offering a range of practical perspectives in different contexts and populations. Appropriate for those new to the topic and to established scholars, this volume explores advocacy in practice as a form of social justice. Bringing together wide-ranging and diverse viewpoints in TESOL, this volume examines the role and of advocacy in a range of contexts, including K-12 classrooms and schools, adult and higher education settings, families and communities, and teacher education programs and professional organizations. Advocacy in English Language Teaching and Learning offers readers a deeper understanding of what advocacy is, what advocacy can be, and gives teacher candidates and educators the tools to advocate for their students, colleagues, and communities"--
Advocacy skills for teachers: "a real careful little dance" / Heather A. Linville -- Problematizing advocacy: definitions, alignments, and expansions / Jamie Harrison and Josephine Prado -- Preparing teacher advocates -- Beyond the philosophy statement: bringing advocacy center stage in TESOL teacher education / James Whiting -- Community asset inquiry: an emerging model for developing ESOL teacher advocacy and reflexivity for family and community engagement / Felice Russell and Amanda Richey -- Building advocacy capacity in a teacher training program / Jamie Harrison -- Cultivating a sense of critical consciousness in teacher candidates within a community-based adult ESL program / Sarina Chugani Molina -- Action research for advocacy in a supervised teaching seminar / Carly Huelsenbeck, Laura Baecher, and Diane Staehr Fenner -- Advocacy in action -- Exploring advocacy in an elementary ESL afterschool program in the United States: empirically, what's there? / Jackie Ridley, Nicole King, Esther Hye-Min Yoon, and Youngjoo Yi -- Language advocate alliances: families and educators united to support English -- Moving away from the margins: publication of international voices as a tool for advocacy / Kristin Roberts-Raymond, Denise Desrosiers, Andrea Paquin, and Carolyn Hutton -- Action required: the adult educator as activist / Rob Sheppard -- A framework for asset-focused advocacy in adult ESL education Deborah Kennedy -- Making the path by walking together: a collaborative approach to advocacy / Sarah Hesson and Rachel Toncelli -- Advocating with specific EL populations -- Advocating for Indigenous Hispanic EL students: promoting the Indigenismo within / Luis Javier Pent'n Herrera -- A mother's advocacy: lessons for educators of long-term EL students / Maneka Deanna Brooks -- From majority to minority: advocating for English learners from the African diaspora / Kisha C. Bryan, Ayanna Cooper, and Babatunji Ifarinu.
HB
Description based on print version record.
Keywords: English language -- Study and teaching -- Foreign speakers; Social advocacy